"Enlarge the site of your tent" :the city as unifying theme in Isaiah : the Isaiah Workshop = De Jesaja Werkplaats - Wieringen, A. L. H. M. van 1963-; Woude, Annemarieke van der. (Oudtestamentische Studiën, Old Testament Studies, 2011)
In the year 2000, the first OTS volume by the Jesaja Werkplaats was published, entitled: Studies in Isaiah 24-27 (OTS 43). In the present volume, the question as to the possible unity of the book Isaiah forms the centre of the Jesaja Werkplaats ' interest. In order to gain a better insight into this question, the Jesaja Werkplaats has decided on a fixed starting point: the concept of the 'city' within the book Isaiah. This concept not only has a literary meaning, but also a historical one. Examining the 'city', therefore, demands various exegetical approaches, overcoming the classical dichotomy between diachrony and synchrony. This volume offers an intriguing variety of contributions on the 'city' throughout the entire book Isaiah.